Cadmium, Copper, Lead and Zinc Levels in the green-lipped Mussel Perna viridis (L.) from the West Coast of Peninsular Malaysia: Safe as Food? - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan (Universiti Putra Malaysia Press, 2005)
Green-lipped mussels, Perna viridis, were collected between 2002-2004, from 10 locations on the west coast of Peninsular Malaysia. The samples were analysed for cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn). The metal concentrations (mg/g dry weight) ranged from 0.11 to 5.55 for Cd, 3.49 to 31.1 for Cu, 1.16 to 18.62 for Pb and 60.51 to 119.5 for Zn. From the public health point of view, these metal concentrations were below the maximum permissible levels set by the Malaysian Food Regulations (1985) and were also below the levels regarded as harmful according to the median international standards for metals in mollusks compiled lJy the FAO of the United Nations. Non-carcinogenic hazard indices of the metals in the mussels in this present study showed that the consumption of the mussels was not risky and any risk is dependent on the amount of mussels consumed and the sites they were collected from.